Sir Banister Fletcher's a history of architecture - Fletcher, Banister; Cruickshank, Dan (Oxford ; Boston : Architectural Press, 1996)
A History of Architecture is the first major work of history to include an overview of the architectural achievements of the 20th Century. Banister Fletcher has been the standard one volume architectural history for over 100 years and continues to give a concise and factual account of world architecture from the earliest times. In this twentieth and centenary edition, edited by Dan Cruickshank with three consultant editors and fourteen new contributors, chapters have been recast and expanded and a third of the text is new. There are new chapters on the twentieth-century architecture of the Middle East (including Israel), South-east Asia, Hong Kong, Japan and Korea, the Indian subcontinent, Russia and the Soviet Union, Eastern Europe and Latin America. The book's scope has been widened to include more architecture from non European countries and coverage of pre twentieth century architecture now includes 6 chapters on Islam
For the first time in Banister Fletcher's A History of Architecture the architecture of the20th century is considered as a whole and assessed in a historical perspective. There is more information on vernacular buildings and engineered structures as well as many new plans and sections. This unique reference book places buildings in their social, cultural and historical settings to describe the main patterns of architectural development, from Prehistoric to the International Style. Again in the words of Sir Banister Fletcher, this book shows that 'Architecture ... provides a key to the habits, thoughts and aspirations of the people, and without a knowledge of this art the history of any period lacks that human interest with which it should be invested.' Winner of the International Architecture Book Award, The American Institute of Architects Book of the Century. THE source book for the historical development of architecture. Publisher's description
The architecture of Egypt, the Ancincent Near east, Asia, Greece and the Hellenistic Kingdoms -- The Architecture of Europe and the Mediterranean to the Renaissance (Rome and the Roman Empire -- Byzantine Empire -- Early Russia -- Early Mediaeval and Romanesque -- Gothic) -- The Architecture of Islam (Seleucid, Parthian and Sassanian -- Umayyad and Abbasic Caliphates -- Local dynastics of central Islam and pre-Moghul India -- Safavid Persia, the Ottoman Empire and Moghul India -- Vernacular building and the Paradise Garden) -- The Architecture of the Pre-Colonial Cultures outside Europe (Africa -- The Americas -- China -- Japana nd Korea -- Indian Subcontinent -- Sout-east Asia) -- The Architecture of the Renaissance and the Post-Renaissance in Europe and Russia (Italy -- France, Span and Portugal -- Austria, Germany and Central Europe -- The Low Countries and Britain -- Russia and Scandinavia -- Post-Renaissance Europe) -- The Architecture of the Colonial and Post-colonial periods outside Europe (Africa -- The Americas -- China -- Japan and Korea -- South-east Asia -- Indian subcontinent -- Australasia) -- The Architecture of the Twenthieth Century (Western Europe 1900-1945 -- Western Europe since 1945 -- Eastern Europe -- Russia and the Soviet Union -- Middle East -- Africe -- North America 1900-1950 -- North American since 1950 -- Latin America -- China -- Japan and Korea -- South-east Asia -- Hong Kong -- Indian Subcontinent -- Oceania)
Includes bibliographical references (pages 1671-1712) and index
Keywords: Architecture -- History; Architecture; History